Achieving high permeability and enhanced selectivity for Angstrom-scale separations using artificial water channel membranes - Shen, Yue-xiao; Song, Woochul; Barden, D. Ryan; Ren, Tingwei; Lang, Chao; Feroz, Hasin; Henderson, Codey B.; Saboe, Patrick O.; Tsai, Daniel; Yan, Hengjing; Butler, Peter J.; Bazan, Guillermo C.; et al. (Nature communications, 2018)
Synthetic polymer membranes, critical to diverse energy-efficient separations, are subject to permeability-selectivity trade-offs that decrease their overall efficacy. These trade-offs are due to structural variations (e.g., broad pore size distributions) in both nonporous membranes used for Angstrom-scale separations and porous membranes used for nano to micron-scale separations. Biological membranes utilize well-defined Angstrom-scale pores to provide exceptional transport properties and can be used as inspiration to overcome this trade-off. Here, we present a comprehensive demonstration of such a bioinspired approach based on pillar[5]arene artificial water channels, resulting in artificial water channel-based block copolymer membranes. These membranes have a sharp selectivity profile with a molecular weight cutoff of ~ 500 Da, a size range challenging to achieve with current membranes, while achieving a large improvement in permeability (~65 L m −2 h −1 bar −1 compared with 4–7 L m −2 h −1 bar −1 ) over similarly rated commercial membranes. Synthetic polymeric membranes used for separations suffer from permeability-selectivity trade-offs. Here the authors demonstrate how a bioinspired pillar[5]arene artificial water channel embedded in a copolymer membrane can improve selectivity while still achieving high permeability.